The concept of a warranty defect in lease contracts according to Algerian civil law - Azeddine, Siar (The International tax journal, 2025)
Explaining the concept of a defect that causes security in the civil lease contract is very important, as it is not possible to investigate the extent of the landlord's commitment to his guarantee unless it is certain that what is tainted by the leased eye is considered a defect that requires guarantee, so the texts of Law No. 07/05 amending and supplementing the Algerian Civil Code have clarified the provisions of defects of the leased eye, and in accordance with this law, we try to shed light on what is meant by the defect that causes the guarantee and the conditions for obliging the lessor to guarantee it. The lessee shall have the right to guarantee the full use of the leased property in return for the rent he pays if it appears to be defective in the legal sense.